Boeravinone B, A Novel Dual Inhibitor of NorA Bacterial Efflux Pump of Staphylococcus aureus and Human P-Glycoprotein, Reduces the Biofilm Formation and Intracellular Invasion of Bacteria - Singh, Samsher; Kalia, Nitin P.; Joshi, Prashant; Kumar, Ajay; Sharma, Parduman R.; Kumar, Ashok; Bharate, Sandip B.; Khan, Inshad A. (Frontiers in Microbiology, 2017)
This study elucidated the role of boeravinone B, a NorA multidrug efflux pump inhibitor, in biofilm inhibition. The effects of boeravinone B plus ciprofloxacin, a NorA substrate, were evaluated in NorA-overexpressing, wild-type, and knocked-out Staphylococcus aureus (SA-1199B, SA-1199, and SA-K1758, respectively). The mechanism of action was confirmed using the ethidium bromide accumulation and efflux assay. The role of boeravinone B as a human P-glycoprotein (P-gp) inhibitor was examined in the LS-180 (colon cancer) cell line. Moreover, its role in the inhibition of biofilm formation and intracellular invasion of S. aureus in macrophages was studied. Boeravinone B reduced the minimum inhibitory concentration (MIC) of ciprofloxacin against S. aureus and its methicillin-resistant strains; the effect was stronger in SA-1199B. Furthermore, time–kill kinetics revealed that boeravinone B plus ciprofloxacin, at subinhibitory concentration (0.25 × MIC), is as equipotent as that at the MIC level. This combination also had a reduced mutation prevention concentration. Boeravinone B reduced the efflux of ethidium bromide and increased the accumulation, thus strengthening the role as a NorA inhibitor. Biofilm formation was reduced by 4–8 folds of the minimal biofilm inhibitory concentration of ciprofloxacin, effectively preventing bacterial entry into macrophages. Boeravinone B effectively inhibited P-gp with half maximal inhibitory concentration (IC50) of 64.85 µM. The study concluded that boeravinone B not only inhibits the NorA-mediated efflux of quinolones but also considerably inhibits the biofilm formation of S. aureus. Its P-gp inhibition activity demonstrates its potential as a bioavailability and bioefficacy enhancer.